The Lithuanian school for young mathematicians: reality and perspective - Antanas Apynis; Eugenijus Stankus; Juozas Šinkūnas (Lietuvos Matematikos Rinkinys)
The history and survey of the activity of the Lithuanian school for young mathematicians is presented.